Analisis Hukum Peninjauan Kembali Terhadap Gratifikasi Penyelesaian Perkara Di Pengadilan (Studi Putusan MA Nomor 1 Pk/Pid.Sus/2019) - Syukri Hidayat Nasution; Zaid Alfauza Marpaung (PMIH Untag Semarang, 2023)
The objective of this research is to methodically and systematically investigate the reality of legal phenomena. This research created normative law by employing legal research methodology. The goal of standard legal research is to find legal doctrines, regulations, or guiding principles that can be used to address legal issues. The objective is to come up with new arguments, hypotheses, or concepts that can be proposed as solutions to the problems that are currently being faced. Other misunderstandings of the word